Porcile - Clementi, Pierre; Citti, Franco 1935-2016; Léaud, Jean-Pierre 1944- (Water Bearer Films, 2003)
<<Der>> Schweinestall
Wide screen format
Orig.: Italien 1969
Enth. a never seen before documentary "Pier Paolo Pasolini"
Keywords: Pasolini, Pier Paolo -- 1922-1975; DVD-Video